PENGARUH HARGA DAN KREDIBILITAS SERTA BRAND PERSONALITY TERHADAP KEPUTUSAN PEMBELIAN GARNIER MEN FACIAL WASH - Rosi Alvia Nurvi Fahlevie; Muhammad Fikry (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
This study aimed to determine the influence of price, credibility, and brand personality on purchase decisions for Garnier men's facial wash in Samarinda. This study used a questionnaire as an instrument and was distributed through a google form. The population was all men from Samarinda. Men of age 24-29 years in Samarinda were enrolled as the study sample, and 150 respondents were obtained using the purposive sampling method, namely a sample selection technique in which an individual selects a sample based on a personal assessment of several characteristics that suit the sample members. The results of multiple regression research based on the F test showed that the significance value was <0.05. It concluded that price, credibility, and brand personality variables simultaneously had a significant influence on purchase decisions for Garnier men's facial wash. Furthermore, the results of the t-test showed that price, credibility, and brand personality variables partially giving positive and significant influence on purchase decisions for Garnier men's facial wash. For the Garnier Men brand, to preserve prices that suit consumers' benefits, maintaining credibility is necessary to cause no disappointment in customers. Also, it can strengthen the brand personality so that consumers are more interested and do not switch over from Garnier Men.